Digital identity for development should keep pace with national cybersecurity capacity: Nigeria in focus. Issue 1 (2nd January 2022) - Okunoye, Babatunde
ABSTRACT : Target 16.9 of the United Nations (UN) Sustainable Development Goals (SDGs) is the provision of legal identity for all, including birth registration by 2030. Approximately 1 billion people globally do not have basic ID credentials. To close this gap, governments in developing countries, including Nigeria, with the backing of international agencies like the World Bank, have launched digital identity schemes for residents. These schemes typically include smart cards which are required to access public and private services. The speed of implementation of these projects has come at the expense of a thorough consideration of cybersecurity and privacy. This is set against the backdrop of the rising threat of cybersecurity breaches in the world against targets such as national identity databases. This paper seeks to provide an overview of digital identity in Nigeria and use the Oxford Global Cyber Security Capacity Centre's Cybersecurity Maturity Model Report 2019 for Nigeria to illustrate how, although progress has been made in key sectors, the implementation of the Nigeria's digital identity programme has progressed faster than cybersecurity maturity in the country. This increases the risk of cyberattacks and opens both the national identity database and users of the digital identity to security vulnerabilities.